2009
DOI: 10.1007/s12640-009-9090-5
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid is Neuroprotective in the Rotenone Rat Model of Parkinson’s Disease: Involvement of α-Synuclein

Abstract: Valproic acid (VPA), an established antiepileptic and antimanic drug, has recently emerged as a promising neuroprotective agent. Among its many cellular targets, VPA has been recently demonstrated to be an effective inhibitor of histone deacetylases. Accordingly, we have adopted a schedule of dietary administration (2% VPA added to the chow) that results in a significant inhibition of histone deacetylase activity and in an increase of histone H3 acetylation in brain tissues of 4 weeks-treated rats. We have tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 59 publications
(88 reference statements)
11
116
0
2
Order By: Relevance
“…Indeed, in Drosophila, toxic nuclear aggregates of α-synuclein interact with histone H3 and promote its deacetylation, possibly through a histone-"masking" mechanism [104]. Consistent with this result, several studies targeting HDAC members through sodium butyrate or valproic acid have shown an increase in histone acetylation, associated with prosurvival and anti-inflammatory effects, and decreased neurotoxicity markers [105][106][107][108][109][110].…”
Section: Pdmentioning
confidence: 73%
“…Indeed, in Drosophila, toxic nuclear aggregates of α-synuclein interact with histone H3 and promote its deacetylation, possibly through a histone-"masking" mechanism [104]. Consistent with this result, several studies targeting HDAC members through sodium butyrate or valproic acid have shown an increase in histone acetylation, associated with prosurvival and anti-inflammatory effects, and decreased neurotoxicity markers [105][106][107][108][109][110].…”
Section: Pdmentioning
confidence: 73%
“…In addition, VPA is neuroprotective in several models of neurodegenerative diseases (Monti et al. 2009, 2010; Chiu et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Observations have shown that a defect in mitochondrial complex I activity may induce the apoptosis of dopaminergic cells, which may contribute to the neurodegenerative process in PD [9] . Administration of rotenone has been used extensively to create PD models to screen for neuroprotective agents both in vivo [10,11] and in vitro [12,13] .…”
Section: Introductionmentioning
confidence: 99%